(untitled) (Palíndromo, 2021)
The paper aims to discuss the motivations connecting me to theoretical and practical research in visual arts that have collective implications. After a brief introduction to my career as an artist-researcher, a contextualization of the theoretical disciplines with which I am involved is presented in order to begin a reflection about the photographic image, in the context of contemporary art, and its production of instants, aligned with an ionic time coherent with its logic of manipulation. The theory of visual possible worlds guides this reflection, in which the notions of “fingere” and “image-fiction” stand out. A case study is presented, based on the work of the artist Éric Baudelaire, who articulates image’s ambiguities in order to reflect on the powers of the false in the re-construction of other versions of the so-called reality. It is concluded that the contemporary (post-)photographic image transits between three degrees: the original event, the historical event and the image event. The latter uses the power of modifying worlds, which the image-fiction carries with it, to stimulate the movement in the direction and the creation of new collective paths.